Investigation of the Relationship between Academic Self-Concept and Academic Self-Efficacy of University Students Receiving Sports Education - Editor, İsa Doğan; Gamze Durmuş (Journal of Educational Issues, 2024)
In this study, it was aimed to examine the relationship between Academic Self-Concept and Academic Self-Efficacy of university students studying in the field of sports sciences. The population of the research consists of a total of 619 students from the 2nd, 3rd, and 4th grades of Karabük University Hasan Doğan School of Physical Education and Sports, while the sample group consists of a total of 241 students, 88 of whom are female and 153 are male. “Personal Information Form”, “Matovu Academic Self-Concept Scale” developed by Liu and Wang (2005) and later adapted for university students by Matovu (2014) and adapted into Turkish by Cantekin and Gökler (2019), and the “Academic Self-Efficacy Scale” developed by Kandemir (2010) were used as data collection tools in the research. The data obtained were analyzed with the SPSS-24 Package Program. At the same time, Pearson correlation analysis, Independent-Samples t-test analysis, One-Way ANOVA (One-Way Analysis of Variance), Tukey multiple comparison were used in the analysis and interpretation of the data. While there is a significant difference between the Academic Self-Efficacy Scale (ASES) and Self-Efficacy for Academic Effort, one of its sub-dimensions, according to the gender of the students, there is no significant difference between it and the other sub-dimensions. According to the grade levels of the students, there is a significant difference between the total of ASES and Self-Efficacy for Handling Academic Problems, one of its sub-dimensions, while there is no significant difference between it and other sub-dimensions.